2006
DOI: 10.1051/0004-6361:20065556
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of the intergalactic UV background towards two lines of sight

Abstract: Aims. We present a reanalysis of the He ii Lyα absorption towards the quasars HS 1700+6416 and HE 2347-4342 using new high S /N, optical observations.Methods. An alternative analysis method is applied, which fits the high quality, optical H i data directly to the He ii spectrum. The results are compared to those inferred from standard line profile analyses. This new method enables us to derive redshift scales characterizing the fluctuations of the column density ratio η. Results. We find η changing smoothly wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 44 publications
5
68
0
Order By: Relevance
“…In that case, η ∼ 40-80 Zheng et al 2004;Fechner et al 2006;Fechner & Reimers 2007) implies r 0 ∼ 110-160 Mpc at z ∼ 2.5. A separate argument comes from matching the (measured) emissivity of the quasar population with the observed optical depth of the He ii forest.…”
Section: Quasars and Radiation Peaks: Finite Lifetimesmentioning
confidence: 95%
See 1 more Smart Citation
“…In that case, η ∼ 40-80 Zheng et al 2004;Fechner et al 2006;Fechner & Reimers 2007) implies r 0 ∼ 110-160 Mpc at z ∼ 2.5. A separate argument comes from matching the (measured) emissivity of the quasar population with the observed optical depth of the He ii forest.…”
Section: Quasars and Radiation Peaks: Finite Lifetimesmentioning
confidence: 95%
“…The best sample so far surrounds the line of sight to HE 2347-4342, whose He ii forest has been extensively studied Shull et al 2004;Fechner & Reimers 2007;Shull et al 2010). Worseck et al (2007) searched for nearby quasars with L min 1-2 × 10 11 L and a maximum impact parameter ∼12 comoving Mpc.…”
Section: Comparison To Existing Observationsmentioning
confidence: 99%
“…Three different analysis methods have been applied to the observations of the He  Lyα forest so far: line profile fitting (Kriss et al 2001;Zheng et al 2004;Fechner et al 2006a), an apparent optical depth method (Shull et al 2004;Fechner et al 2006a) and spectrum fitting (Fechner & Reimers 2007). The latter fits the high-quality optical H  spectrum directly to the He  data, and allows to estimate the length scales of η variations.…”
Section: Methodsmentioning
confidence: 99%
“…There are several suggestions for a physical explanation of this correlation like self-shielding and shadowing effects (Maselli & Ferrara 2005;Tittley & Meiksin 2006) and the spatial distribution of QSOs as the sources of hard radiation (Bolton et al 2006). However, Fechner & Reimers (2007) suggested that part of the correlation might be due to the unjustified assumption that the line widths of the absorption features are dominated by purely turbulent broadening. If this assumption is incorrect, a correlation between the η value and the absorber density will be introduced artificially.…”
Section: Send Offprint Requests To: C Fechnermentioning
confidence: 99%
See 1 more Smart Citation